Comparative analysis of systemic and regional analgesia effectiveness in wounded with combat surgical trauma of extremities at the stages of medical evacuation - Tymchyshyn, D.; Budniuk, O.; Kalchev, M.; Palvashov, R.; Vastyanov, M. (Journal of Education, Health and Sport, 2026)
Combat surgical trauma of the extremities is accompanied by a pronounced pain syndrome, which requires effective control at all stages of medical evacuation. Regional anesthesia is considered a promising component of multimodal analgesia. The purpose of the study was to evaluate the effectiveness of different perioperative analgesia regimens in wounded with combat surgical trauma of the extremities. The prospective study included: patients of Group 1 (n=50) received general anesthesia with systemic analgesia, patients of Group 2 (n=50) – combined anesthesia with regional blocks. Pain intensity was assessed at four stages. Upon admission, pain level was 7 points (6; 8) without intergroup differences (p=0.57). After surgery, pain was significantly lower in Group 2 – 1 point (1; 2) vs 3 points (3; 4) (p<0.05). At the evacuation stage, values were: 1 point (1; 2) and 3 points (2; 3), respectively (p<0.05). After transportation, the difference persisted: 1 point (1; 2) vs 5 points (4; 6) (p<0.05). Intraoperative fentanyl consumption was lower (0 vs 0.3 mg), as well as propofol (3.3±0.7 vs 8.5±1.2 mg/kg/h). Awakening time was 0 min vs 10 min. Opioids in the postoperative period were used in 6% of patients in Group 2 vs 74% of patients in Group 1, and during transportation – in 6% vs 24%, respectively. Regional analgesic blocks provide more effective pain control, reduce the need for opioids, and improve the course of the postoperative period in wounded with combat surgical trauma of the extremities.